Metaphor in Poetry Matahari dalam Hujan by Rika - Kamariah Kamariah; Johan Arifin (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
This research focuses on the use of metaphors contained in the collection of poems by Rika. The aim is to describe the type, function and meaning of the metaphor in the collection of poems. The research method used is a descriptive analysis method with a structural approach. There are four types of metaphors found in the poetry of the Park Lights Man and Which Map You Are Going to in a collection of Rika's poetry entitled Sun in the Rain. (a) Anthropomorphic metaphors are found in both poetry, as many as three lines, (b) animal metaphors are also found in both poems, as many as four lines, (c) synestetic metaphors are only found in LLT poetry by one array, and (d) abstract to concrete metaphors found in both poems, as many as seven lines . Three metaphorical functions include, (a) overcoming the shortcomings and limitations of lexicons or expressions found only in one line of LLT poetry, (b) expressing speech found in both poems, as many as ten lines, and (c) avoiding the saturation found in both poems, as many as five lines. Whereas the meaning of metaphor is as much as two meanings, which include, (a) the meaning of living metaphor of nine arrays, and (b) the meaning of dead metaphor of five arrays. Abstrak Penelitian ini berfokus pada penggunaan metafora yang terdapat pada kumpulan puisi Karya Rika. Tujuannya adalah untuk mendeskripsikan jenis, fungsi dan makna metafora pada kumpulan puisi tersebut. metode penelitian yang digunakan adalah metode deskriptif analisis dengan pendekatan struktural.Ada empat jenis metafora yang ditemukan dalam puisi Lelaki Lampu Taman dan Peta Mana yang Kau Tuju yang terdapat dalam kumpulan Puisi karya Rika yang berjudul Matahari dalam Hujan.(a) metafora antropomorfis ditemukan di kedua puisi, sebanyak tiga larik,(b) metafora binatang juga ditemukan di kedua puisi, sebanyak empat larik, (c) metafora sinestetik hanya ditemukan pada puisi LLT sebanyak satu larik,dan (d) metafora abstrak ke konkret ditemukan dikedua puisi, sebanyak tujuh larik. Tiga Fungsi metaforameliputi, (a) mengatasi kekurangan dan keterbatasan leksikon atau ungkapan hanya ditemukan pada puisi LLT sebanyak satu larik,(b) mengekspresikan tuturan ditemukan dikedua puisi, sebanyak sepuluh larik, dan (c) menghindari kejenuhan ditemukan dikedua puisi, sebanyak lima larik. Sedangkan makna metafora sebanyak dua makna, yakni meliputi, (a) makna metafora hidup sebanyak sembilan larik, dan (b) makna metafora mati sebanyak lima larik. Kata kunci: metafora, jenis, fungsi, makna, puisi